Shariʿa, Justice and Legal Order : Egyptian and Islamic Law: Selected Essays - Peters, Rudolph, (Studies in Islamic Law and Society ;, 2020)
In Shariʿa, Justice and Legal Order: Egyptian and Islamic Law: Selected Essays Rudolph Peters discusses in 35 articles practice of both Shariʿa and state law. The principal themes are legal order and the actual application of law both in the judiciaries as well in cultural and political debates. Many of the topics deal with penal law. Although the majority of studies are situated in the Ottoman and, especially, Egyptian period, few of them are of another region or a more recent period, such as in Nigeria or, also, Egypt. The book's historical studies are mainly based on archival judicial records and are definitively pioneering. Although the selected articles of this book are the fruit of more than forty years of research, most of them have constantly been cited.